Highly Selective Transport of Silver(I) Cation Across a Bulk Liquid Membrane Containing an Acyclic Thioether Ligand as Carrier - Fahmideh-Rad, E.; Hossein Rounaghi, Gholam; Arbab-Zavar, M.H.; Chamsaz, Mahmoud (Asian Journal of Chemistry, 2010)
A 1,2-dichloroethane bulk liquid membrane system containing a new synthetic acyclic thioether ligand, i.e. 2,9-dihydroxy-1,10-diphenoxy-4,7-dithia decane; (C20H26O4S2) and palmitic acid was used for highly selective and efficient transport of Ag+ cation. The transport process was maintained by the buffering the source and receiving phases. For these systems that displayed transport behaviour, sole selectivity for Ag+ cation was observed under the employed experimental conditions. In the presence of thiosulfate ion (S2O32-) as suitable metal ion acceptor in the receiving phase, the amount of Ag+ cation transported across the liquid membrane after 4 h was (90.2 ± 2.0 %). The membrane solvents include: 1,2-dichloroethane (1,2-DCE), chloroform (CHCl3), dichloromethane (DCM), nitrobenzene (NB) and nitromethane (NM). The results show that the sequence of transport efficiency for Ag+ cation in organic solvents is: 1,2-DCE > CHCl3 > DCM > NB > NM. The experimental variables such as the concentration of carrier in the membrane phase, the nature and concentration of fatty acids in the membrane phase, the nature and concentration of the stripping agents in the receiving phase, receive phase volume and the effect of other parameters such as pH of source and receiving phases and the time of transport were optimized in order to achieve the highest transport efficiency of a 5 × 10-4 M solution of Ag+ cation across the bulk liquid membrane systems. The proposed transport method is simple, rapid, selective and reproducible compared with the other methods of separation.